GAGAL JANTUNG DENGAN FRAKSI EJEKSI SEDIKIT MENURUN: SUATU TINJAUAN PUSTAKA - Sidhi Laksono (Universitas Ciputra Surabaya, 2023)
The European Heart Association (ESC) 2021 heart failure guidelines introduce a third ejection fraction (EF) category for heart failure with an EF of 40-49%, referred as heart failure with mildly reduced EF (HFmrEF). This category has not been explored much in comparison to heart failure with reduced EF (HFrEF; defined as EF < 40%) and heart failure with normal EF (HF preserved EF, HFpEF; defined as EF 50%). The prevalence of HFmrEF in the population of patients with HF was 10-25%. HFmrEF may be underdiagnosed, given the error and variability in EF measurements and the presence of milder symptoms in these patients compared to patients with HFrEF. The precise recognition and phenotyping of HFmrEF is important as it may support treatment recommendations based on available data. One study showed that survival rate in patients with HFmrEF or HFrEF is lower compared to patient with HFpEF. The characteristics of HFmrEF are more similar to HFrEF. Further studies are needed to fill the information gap in the case of HFmrEF.